2005
DOI: 10.1007/s11232-005-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-point function in the minimal Liouville gravity

Abstract: The problem of the structure constants of the operator product expansions in the minimal models of conformal field theory is revisited. We rederive these previously known constants and present them in the form particularly useful in the Liouville gravity applications. Analytic relation between our expression and the structure constant in Liouville field theory is discussed. Finally we present in general form the three-and two-point correlation numbers on the sphere in the minimal Liouville gravity. Liouville g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
280
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(297 citation statements)
references
References 23 publications
(37 reference statements)
15
280
0
2
Order By: Relevance
“…The expression (A.16) coincides with the formula given in [43]. The normalised structure constants D are invariant under permutation of the variables d i .…”
Section: Jhep09(2007)098supporting
confidence: 68%
See 1 more Smart Citation
“…The expression (A.16) coincides with the formula given in [43]. The normalised structure constants D are invariant under permutation of the variables d i .…”
Section: Jhep09(2007)098supporting
confidence: 68%
“…Recently this limit was investigated in [42], and it was argued that only for p = 1 a physically sensible three-point function is obtained. The relation of the resulting theory to minimal models or generalised minimal models [43,44] is unclear until now. The continuation of Liouville theory to other, non-rational central charges c < 1 is more singular, and it is clear that the structure constants do not have a well-defined limit as functions of the field parameters, though it might be that one can find a sensible limit in terms of distributions.…”
Section: Jhep09(2007)098mentioning
confidence: 99%
“…In the following we will show that indeed three-point number and conformal blocks of this CFT arise as building blocks of the supersymmetric partition function of N = 2 U(2) gauge theory on S 2 × S 2 . Liouville Gravity (LG) [29,30] is a well-known two-dimensional theory of quantum gravity composed of three CFT sectors 1. Liouville theory sector, which has a central charge…”
Section: Jhep07(2015)054mentioning
confidence: 99%
“…The former have been computed in [29] (eq.7.9) for three generic dressed operators U α i and can be written in terms of γ function, see eq. (E.11), as…”
Section: Jhep07(2015)054mentioning
confidence: 99%
“…To this end, note that in [4], a supersymmetric theory was constructed on S 2 × S 2 , and its partition function was computed using the technique of localization. The authors observed that the building blocks of the partition function contained three-point functions and conformal blocks of Liouville gravity [5,6], and so they conjectured a novel AGT-like correspondence between the 4d supersymmetric theory on S 2 × S 2 and 2d Liouville gravity.…”
Section: Jhep05(2017)121mentioning
confidence: 99%